INTEGRATED WASTE TREATMENT: Solutions and Utilization of Waste with Economic Value - Teguh Wiyono; Karina Dewi (Jurnal PKM Manajemen Bisnis, 2023)
Garbage is one of the old problems that has not been resolved, the poor awareness of the Indonesian people is one of the causes. However, along with the magnitude of the negative impact of waste on human life, it requires the attention and efforts of all parties. In this regard, as an educated society, it has contributed to the problem. Therefore, this service activity is carried out, in the form of counseling and waste processing practices. This is done in order to raise public awareness of the waste problem, which must be solved together. This activity was carried out in the waste processing community in the city of South Tangerang which is part of the Ganespa organization. There were 20 participants in the activity, and it was carried out on Saturday, May 21, 2022. This activity was packaged in the form of socialization, discussion, question and answer, and practice of sorting waste based on groups and their benefits. As a result of this activity, it turns out that waste with economic value is more responsive than other types of waste. Waste with economic value is generally in the form of plastic, paper, and iron. However, the participants were also enthusiastic about processing organic waste which can be processed into fertilizer or compost for plants. Even organic waste from vegetable and fruit waste can be used as livestock feed, such as maggot food, catfish, and so on.